2012
DOI: 10.1111/j.1600-0404.2012.01705.x
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic lateral sclerosis in Sardinia (Italy): epidemiologic features from 1957 to 2000

Abstract: Objectives To evaluate epidemiological variables of amyotrophic lateral sclerosis (ALS) in Sardinia (Italy) in the 1991–2000 periods and compare them with the preceding decades. Material and methods Survey, critical reappraisal or clinical re‐evaluation of all ALS cases with onset in the decade 1991–2000; calculation of crude and age‐adjusted incidence, duration of disease, survival rates and the latency between onset of symptoms and diagnosis. Results A significant increase in the mean annual incidence was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
(148 reference statements)
1
5
0
Order By: Relevance
“…The male to female ratio was 1.63:1 in this study, which was consistent with other reports . It had been suggested that many factors may be responsible for this observed ratio, including: possible protective hormonal factors in women or the increased likelihood of men being exposed to putative risk factors like trauma, occupational exposure, physical activity, and smoking . However, a much younger age at onset was found for women in this study, which suggests that the protective role of female hormones in ALS may not be as important as previously thought, and that other factors may play a key role in the pathogenesis of ALS .…”
Section: Discussionsupporting
confidence: 89%
“…The male to female ratio was 1.63:1 in this study, which was consistent with other reports . It had been suggested that many factors may be responsible for this observed ratio, including: possible protective hormonal factors in women or the increased likelihood of men being exposed to putative risk factors like trauma, occupational exposure, physical activity, and smoking . However, a much younger age at onset was found for women in this study, which suggests that the protective role of female hormones in ALS may not be as important as previously thought, and that other factors may play a key role in the pathogenesis of ALS .…”
Section: Discussionsupporting
confidence: 89%
“…A further research into the family history was performed on the control individuals who tested positive for the mutation. These control individuals, also re-evaluated both clinically and cognitively, were resubjected to a careful collection of family history, from which it emerged, thanks to our archives and our previous clinical studies [9], that two of them had relatives with ALS and two relatives with FTD.…”
Section: Resultsmentioning
confidence: 99%
“…Additional prospective, population-based studies have come out of Italy, including reports for ALS epidemiology in Liguria [72], Sardinia [73, 74], and Sicily [75]. Incidence rates (95% CI) ranged from 1.33/100,000 (not reported) [73] to 3.22/100,000 (2.66–3.90) [72], which are consistent with the rates published in the Italian reports included in this review. Kihira [76] published a 5-decade review of the changes in ALS incidence on the Kii Peninsula of Japan.…”
Section: Discussionmentioning
confidence: 99%